A three-dimensional formulation for levy-type transversely loaded cross-ply shell panels. (1st February 2020) - Ahmadi, Isa
Highlights: A three-dimensional formulation is developed to analyze the stresses in composite panel under transverse loading. An analytical solution is presented for the governing equations. The presented formulation demonstrate high stress gradient for interlaminar stresses near the free and clamped edges. Numerical predictions for out of plane stresses satisfy the traction conditions on the top and bottom surface of the panel. The effect of radius to thickness, width to thickness ratio and boundary conditions are investigated on edge stresses. Abstract: In this study, a formulation is developed for investigation of three-dimensional edge stresses in cylindrical composite shell panels under distributed transverse loading. The formulation is obtained by employing the Galerkin weak formulation of the equilibrium equations. The obtained governing equations for the panel are solved via an analytical method for Levy-type boundary conditions including free and clamped edges. The presented formulation is capable of prediction of three-dimensional and boundary layer stresses in the composite panels subjected to transverse loading. The edge stresses in free edge, clamped edge and simple edge of transversally loaded cylindrical composite panel are studied. Comparison of numerical results with the available results of exact elasticity solution in the literature confirms the accuracy and the efficiency of the formulation. Graphical abstract: Image, graphical abstract